2005
DOI: 10.1590/s0037-86822005000600018
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento de gestantes com toxoplasmose em serviços públicos de saúde

Abstract: RESUMOÉ discutido o monitoramento de 290 gestantes com suspeita de toxoplasmose aguda atendidas em serviços públicos. Em 69% um único teste (ELISA-IgM) conduziu ao tratamento. De 112 tratadas, o sistema não disponibilizou medicamento para 24%. Em 12,1% houve aumento progressivo de IgM e IgG. Em 48,2%, o tratamento foi iniciado trinta dias após o diagnóstico laboratorial. Palavras-chaves: Gestantes. Toxoplasmose. Pré-natal. Monitoramento. ABSTRACTThe monitoring of 290 pregnant women with suspicion of acute toxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Since the avidity indexes were identical to those of the maternal serum and the methods used in this study were unable to differentiate IgG antibodies from mothers and babies, it can be assumed of the fetuses can become infected. 13,14,16 The fetuses of these two pregnant women were probably not infected during gestation, although this condition is not conclusive. There have been reports that 70% of newborns infected during gestation do not present symptoms at birth.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since the avidity indexes were identical to those of the maternal serum and the methods used in this study were unable to differentiate IgG antibodies from mothers and babies, it can be assumed of the fetuses can become infected. 13,14,16 The fetuses of these two pregnant women were probably not infected during gestation, although this condition is not conclusive. There have been reports that 70% of newborns infected during gestation do not present symptoms at birth.…”
Section: Discussionmentioning
confidence: 91%
“…10 Additionally, Brazilian studies have demonstrated that infection rates among pregnant women vary according to the geographical region. [10][11][12][13][14][15][16] However, there are only a few studies evaluating anti-T. gondii antibodies and their avidity in mothers and their newborns in the state of For ELISA, the crude extract of tachyzoites was obtained as previously described. 21 The parasites were sonicated (10 cycles of 1.0 A/minute for five minutes with two-minute intervals).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of implanting maternal serum screening to detect toxoplasmosis lies in the possibility of adopting prophylactic and therapeutic measures to minimize the vertical transmission and/or decrease the damage to fetus development 15 . In the face of the seriousness of the congenital disease, it is fundamental to start prenatal care in the first three months of pregnancy, so that, acute cases of congenital toxoplasmosis can be early identified 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The maternal serum screening for detection of toxoplasmosis is an important tool, which allows the adoption of early prophylactic and therapeutic measures, thus reducing the rate of vertical transmission and/or fetal development impairment 18 . Therefore, it is essential to start the prenatal care in the first trimester of pregnancy, performing the serological screening, allowing the early identification of acute cases of gestational toxoplasmosis 19 .…”
Section: Maternal Screening Programsmentioning
confidence: 99%